การศึกษาประสิทธิภาพและความคุ้มทุนของระบบผลิตไฟฟ้าด้วยเซลล์แสงอาทิตย์ที่ติดตั้งบนหลังคา (PERFORMANCE AND ECONOMIC ANALYSIS ON ROOFTOP PV SYSTEM) - ทองสุก, สุรกิจ; เง่าพิทักษ์กุล, อรรถพล (Srinakharinwirot University Journal of Sciences and Technology, 2018)
This paper presents performance analysis of rooftop pv system on building study case. Actual data obtained from measurement at installation site will be compared to calculation data from PVSYST software in order to study factors that have an effect on power system efficiency. After that, economic analysis to evaluate the feasibility of investment in the proposed systems is studied. Installation costs and energy generation capacity are employed to calculate discount payback period and internal rate of return. Results indicate that the actual system can provide energy close to the simulation system. The amount of energy generated from the photovoltaic system can improve the total energy consumption of the building.